PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) PADA PEMBELAJARAN MATEMATIKA SISWA - I Made Surat; I Gusti Made Ayu Anggun Tiara Pratini (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Mathematics is one subjects taught at all levels and types of formal education with a major contribution to various fields such as technology, industry, finance, and so on. However, mathematics is not a subject that are interested because difficult, scary, uninteresting and boring. This mindset creates negative impressions and experiences. Therefore, teachers should use appropriate models, strategies, methods and approaches so that they can build and improve positive attitudes towards mathematics. The aim of this research is to determine the application of the Team Games Tournament (TGT) type cooperative learning model in mathematics learning for students in class VII H at SMPN 8 Denpasar. The TGT model allows students to learn to collaborate, compete and be responsible while still being guided by learning objectives. This research uses test and non-test instruments in the form of observation sheets, interviews and student learning outcomes tests. The results of this research were that in Cycle I the percentage of students who completed was 56.10%, then increased in Cycle II with a completion percentage of 80.49%. Therefore, it can be said that TGT type cooperative learning can improve the learning outcomes of class VII H students at SMPN 8 Denpasar.